Foliar fungal pathogens of European woody plants in Siberia: an early warning of potential threats?. Issue 5 (12th March 2013) - Tomoshevich, M.; Kirichenko, N.; Holmes, K.; Kenis, M.; Stenlid, J.
Summary In this article, we report observations made during thirteen years on foliar fungal pathogens attacking European and Eurasian woody broadleaved species in Siberian arboreta and cities and discuss the possibility of using such data for detecting exotic pathogens that may represent a danger for European tree and shrub species, should these pathogens be introduced into Europe. A total of 102 cases of symptomatic infections (fungus‐host plant associations) involving 67 fungal species were recorded on 50 of the 52 European and Eurasian woody plant species. All but four of the fungi found during the surveys were previously reported in Europe. However, 29 fungus–host plant associations are apparently new to science, suggesting that complexes of cryptic species differing in their host range and geographic range may occur. Seventeen percentage of associations were given a high damage score, that is, more than 50% of plant area was attacked, for at least some localities. In nearly half of the cases, fungus–host plant associations were found to be very frequent, that is, occurring every year and at all locations where the plant was inspected. A list of pathogen–host associations in Siberia deserving further investigation is provided, either because the pathogen is not yet recorded in Europe or because the pathogen–host association has not yet been reported, and the damage is high or, finally, because the damage and infestation level is unusually high in known associations. Further studies should involve molecular characterization of these foliar pathogens and their host range testing.